Pengaruh Harga Dan Mutu Terhadap Penjualan Sepeda Motor Matic Honda Studi Kasus Pada Karyawan Di PT. Anteraja Jakarta Barat - Erika Bening Islamiaty; Abdul Muslim (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to analyze the effect of price and quality on sales of Honda automatic motorcycles (a case study on employees at PT Anteraja West Jakarta). This research is a quantitative research. A sample of 105 respondents was taken using a simple random sampling technique. Data was analyzed using multiple regression analysis, T test, F test and the coefficient of determination. The results of the study based on the T test and F test showed that Price had a significant but not significant effect on Sales, while and Quality had a positive and significant effect on Sales. In this study, the coefficient of determination (R2) was 0.708, meaning that the effect of the price and quality variables on sales was 70.8%, with the remaining 29.2% being the influence of other variables not examined in this study.